Desarrollo de un Recubrimiento Comestible Natural a base de Mucílago de Chía (salvia hispánica l) y Aceite Esencial de Naranja (Citrus × aurantium) - Robayo Garzón, Diana Carolina (2018)
The Strawberry (Fragaria vesca) is one of the most perishable fruit, because their high respiratory rate and the lack of shell that protects the quality of the fruit. The present research job had as object the development of natural edible coating based on mucilage chía and essential oil of orange applied in the strawberry as a post harvest process. The research was conducted in the laboratory of Agroindustrial engineering food analysis, strawberries with the natural edible coating were stored at 12 ° C for a period of 12 days performing the analysis on days 1, 5, 10, and 12. To determine the best treatment was an experimental design DBCA in accordance with factorial of A by B with 2 replicates in which the T4 with 70% formulation mucilage, 20% of essential oil orange, 10% solution of gelatin and water was identified as the best tratament. In addition, the coating has antibacterial and antifungal activity which allows the reduction of the percentage of weight loss, the respiratory rate of the strawberry and conservation of the properties of the fruit. An evaluation of the stability of strawberries with the edible coating against a witness, where discussed the organoleptic characteristics, degrees brix, microbiological quantification, pH and titratable acidity, the strawberry witness present a time life of 5 days while that in the coated Strawberry was a life time of 12 days while maintaining optimal conditions for human consumption.